COVID-19 Stress Perception, Resilience, and Well-Being Among Nurse Practitioners in the Post-Pandemic Era: A Cross-Sectional Study - Lin, Wen-Di; Wu, Pei-Ling; Pai, Hsiang-Chu (PT. Pubsains Nur Cendekia, 2026)
Background: The COVID-19 pandemic imposed sustained psychological stress on healthcare professionals, including Nurse Practitioners (NPs). In the post-pandemic era, understanding how perceived pandemic-related stress, resilience, and well-being interact is crucial for supporting workforce sustainability and mental health. Aims: To examine the relationships between perceived COVID-19 stress, resilience, and subjective well-being among NPs in Taiwan and identify key predictors of well-being. Methods: A cross-sectional correlational design. Online survey data were analysed and collected from 254 Taiwanese NPs between June and September 2023 using the Perceived Stress Scale of COVID-19, Resilience Scale for Adults, and Subjective Well-Being Scale. Data were analyzed using descriptive statistics, Pearson’s correlation, and multiple linear regression. Results: The regression model explained a significant portion of the variation in subjective well-being (R² 65.5%; adjusted R² = .655). Perceived COVID-19 stress was negatively associated with resilience (r = –.394, p < .01) and subjective well-being (r = –.373, p < .01). Resilience was strongly and positively correlated with well-being (r = .802, p < .01) and emerged as the strongest predictor in regression analysis (β = .802, p < .001). Perceived stress did not significantly predict well-being (p = .259). Conclusion: Nursing managers can incorporate resilience-enhancing strategies, such as stress management workshops, mentoring programs, peer support, and reflective practices, into organisational policies to strengthen workforce sustainability.